X² + 3x = 10
Convert to standard form.
x² + 3x - 10 = 0
factor x² = x * x
factor -10 = 5 * -2
(x + 5) (x - 2) = 0
x(x -2) + 5(x-2) = 0
x² - 2x + 5x - 10 = 0
x² + 3x - 10 = 0
x + 5 = 0 x² + 3x = 10
x = -5 -5² + 3(-5) = 10
25 - 15 = 10
10 = 10
x - 2 = 0 x² + 3x = 10
x = 2 2² + 3(2) = 10
4 + 6 = 10
10 = 10
Answer:
7x(x−1)
Step-by-step explanation:
3 * ln 4x = 13
<span><=> </span>
<span>ln 4x = 13/3 </span>
<span><=> </span>
<span>4x = e^(13/3) </span>
<span><=> </span>
<span>x = e^(13/3) / 4 </span>
<span><=> </span>
<span>x ~ 19.05 </span>
Answer:
6
Step-by-step explanation:
the top and the bottom line on the squares and with the top and the bottom line on both of the arrows